William J. Baumol, Robert E. Litan and Carl J. Schramm. Good Capitalism, Bad Capitalism and the Economics of Growth and Prosperity. New Haven: Yale University Press, 2007. 321 pp. (The Pakistan Development Review, 2009)
The central idea of the book is that Capitalism has many forms—some good, others bad, with entrepreneurial capital being the best. The authors argue that the spectacular economic performance of the developed world is owed to the ‘good capitalism’ practised over there and that the blame for the poor performance of many economies must lie with one or the other kind of ‘bad capitalism’, that these economies continue to practise. The authors identify policy tools that can help countries in making a transition from ‘bad capitalism’ to ‘good capitalism’. The introductory chapter ‘Entrepreneurship and Growth’ gives an overview of the key elements of an entrepreneurial economy. In the next chapter, the authors question ‘Why Economic Growth Matters’ and convincingly rebuff those who question the virtues of growth. To those who put limits on growth the authors’ answer is: “the same process of technological advancement that undermined Malthus’ dire prediction about population growth may be able to quiet the concerns of modern day Malthusians who worry about disappearing energy”. Chapter 3 conducts a comprehensive review of modern growth theories with special focus on innovation and institutions. After reviewing the work of Solow, the authors move directly to the influence of institutions on growth. They argue that institutions take time to develop and that growth depends on ‘home grown’ institutions. The long time required to develop growth promoting institutions may explain why dictators have been successful in Korea and Singapore in boosting growth, while the time horizon of the politician is shorter, at best extended up to the next elections. The authors’ emphasis upon ‘home grown’ institution is also a verdict against the Washington Consensus.